Effect of solvent quality and sidechain architecture on conjugated polymer chain conformation in solution - Ma, Guorong; Li, Zhaofan; Fang, Lei; Xia, Wenjie; Gu, Xiaodan (Nanoscale, 2024)
Conjugated polymers (CPs) are solution-processible for various electronic applications, where solution aggregation and dynamics could impact the morphology in the solid state. Various solvents and solvent mixtures have been used to dissolve and process CPs, but few studies have quantified the effect of solvent quality on the solution behavior of CPs. Herein, we performed static light scattering and small-angle X-ray scattering combined with molecular dynamics (MD) simulation to investigate CP solution behaviors with solvents of varying quality, including poly(3-alkylthiophene) (P3ATs) with various sidechain lengths from -C 4 H 9 to -C 12 H 25 , poly[bis(3-dodecyl-2-thienyl)-2,2′-dithiophene-5,5′-diyl] (PQT-12) and poly[2,5-bis(3-dodecylthiophen-2-yl)thieno[3,2- b ]thiophene] (PBTTT-12). We found that chlorobenzene is a better solvent than toluene for various CPs, which was evident from the positive second virial coefficient A 2 ranging from 0.3 to 4.7 × 10 −3 cm 3 mol g −2 towards P3ATs. For P3ATs in non-polar solvents, longer sidechains promote more positive A 2 , indicating a better polymer-solvent interaction, wherein A 2 for toluene increases from −5.9 to 1.4 × 10 −3 cm 3 mol g −2 , and in CB, A 2 ranges from 1.0 to 4.7 × 10 −3 cm 3 mol g −2 when sidechain length increases from -C 6 H 13 to -C 12 H 25 . Moreover, PQT-12 and PBTTT-12 have strong aggregation tendencies in all solutions, with an apparent positive A 2 (∼0.5 × 10 −3 cm 3 mol g −2 ) due to multi-chain aggregates and peculiar chain folding. These solvent-dependent aggregation behaviors can be well correlated to spectroscopy measurement results. Our coarse-grained MD simulation results further suggested that CPs with long, dense, and branched sidechains can achieve enhanced polymer-solvent interaction, and thus enable overall better solution dispersion. This work provides quantitative insights into the solution behavior of conjugated polymers that can guide both the design and process of CPs toward next-generation organic electronics. The solubilization of conjugated polymers can be carefully quantified using static light scattering. Our findings reveal that the architecture of sidechains and backbones significantly influences polymer's conformation and aggregation.